When I Encountered Difficult Problems - Akasofu, Syun-Ichi (Frontiers in Astronomy and Space Sciences, 2022)
All of us encounter our unique difficulties as scientists. Although the kind of difficulty varies by scientist, I describe my own in this program, and explain how I responded, together with a sort of moral. They are: (a) When theorists seemed to encounter a deadlock, (b) When a well-accepted theory is confronted with a seriously contradictory observational fact, (c) When there is a generally believed morphology of a phenomenon that does not agree with my observations, (d) When a single approach or theory prevails, but I have a different idea. Obviously, my responses are just an attempt, which will be judged by future developments in space physics.